Adsorção de CO2 em carvão ativado produzido a partir de endocarpo de coco (Cocos nucifera L) - Araújo, Paulo Cardozo Carvalho de (2018)
A well-established issue in the field of industrial pollution control comes to the fore with a major focus on global scientific research: the separation of carbon dioxide from gaseous currents, known as capture and sequestration of CO2, in order to avoid atmospheric concentration, since this pollutant intensifies the greenhouse effect. In this context, the use of CO2 capture systems based on adsorption is the focus of several research projects, all aiming to reconcile the synthesis of low cost adsorbent materials with the high performance in the capture of carbon dioxide. In this work, the CO2 adsorption by the produced activated carbon from the coconut endocarp (Cocos nucifera L.) was studied, which was characterized by Fourier transform infrared spectroscopy (FTIR), X-ray fluorescence (FRX), quantification of acidic and basic groups by Boehm method, scanning electron microscopy (SEM), specific area of BET, thermoanalytical analysis, determination of humidity, pH and ash. Adsorption tests were carried out by static volumetric technique in a fixed bed column, with online acquisition of system pressure data with a precision of 10-4 bar, at temperatures of 15, 24 and 35 ° C and initial pressure of 1.4 till 3.4 bar. The evaluation of the CO2 removal equilibrium was done by analyzing the adsorption isotherms, to which the experimental data showed a better fit for the Langmuir model. The time required to reach adsorbent saturation was 1500 seconds, determined from the kinetic curves, and the pseudo second order model was the best fit for the experimental data. The produced activated carbon presented a good CO2 adsorption capacity, which may be related to the nature of the surface area, and to the presence of organic and inorganic groups capable of promoting chemical interactions with carbon dioxide, being inversely proportional to the increase of the adsorption bed, with the highest adsorbed amount found being 76.03 mg g -1 at 15° C. The results obtained through the regeneration cycles showed that the regenerative temperature range from the thermal analysis of the coal was a parameter that confirmed the viability of the adsorbent produced, which maintained the adsorptive capacity after three consecutive adsorption / desorption cycles.